2003
DOI: 10.1021/jf0259821
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Activity in White and Red Wine Extracts

Abstract: Red wine is enriched in resveratrol, trans-3,5,4'-trihydroxystilbene, a compound in grape skin that inhibits the development of pre-neoplastic lesions in mouse mammary tumor cells in culture and inhibits cancer cell proliferation in vitro. Grapes also contain other bioactive compounds including flavonoids, flavans, and anthocyanins. The estrogenic activities of extracts prepared from one white (Freie Weingärtner Wachau, Grüner Veltliner, Austria) and two red wines (Woodbridge, Cabernet Sauvignon, California; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…Klinge et al (2003) detected a maximum 84 ng/l EEQ in red wine. Promberger et al (2001) calculated 23-41 ng/l EEQ for beer, a result that was confirmed by Takamura-Enya et al (2003), who detected an estrogenic potency of approximately 30 ng/l EEQ in beer; extracts from soy based food (miso, tofu, and soy sauce) and coffee also contained EEQ in low nanogram per liter range.…”
Section: Discussionmentioning
confidence: 97%
“…Klinge et al (2003) detected a maximum 84 ng/l EEQ in red wine. Promberger et al (2001) calculated 23-41 ng/l EEQ for beer, a result that was confirmed by Takamura-Enya et al (2003), who detected an estrogenic potency of approximately 30 ng/l EEQ in beer; extracts from soy based food (miso, tofu, and soy sauce) and coffee also contained EEQ in low nanogram per liter range.…”
Section: Discussionmentioning
confidence: 97%
“…However, resveratrol was originally characterized as a phytoestrogen on the basis of its ability to bind ERs. 166 Because studies indicate that an average consumer is capable of absorbing physiological quantities of resveratrol from normal red wine intake, molecular characterization is necessary. Resveratrol exists as cis-and trans-isomers; the trans-isomer mediates most of its biological actions.…”
Section: Resveratrolmentioning
confidence: 99%
“…168 Resveratrol demonstrates genomic activity as indicated by activation of an ERE-luciferase reporter in transiently transfected Chinese hamster ovary K1 (CHO-K1) cells but shows higher activation with ER␤ than ER␣ consistent with other phytoestrogen compounds like genistein. 166 Nongenomic activity of resveratrol has also been described. In a recent study, resveratrol inhibited androgenand ER␣-dependent PI3-K activities in prostate cancer cell lines.…”
Section: Resveratrolmentioning
confidence: 99%
“…Furthermore, RS inhibits the enzyme cyclooxygenase-1, which is a strong vasoconstrictor and has an important role in platelet aggregation (Szewczuk et al, 2004). Increased activity of nitric oxide synthase was found in pulmonary artery endothelial cells when treated with RS, which indicates the direct association of nitric oxide in vasorelaxation (Klinge et al, 2003). RS has been shown to increase the expression of nitric oxide synthase and hence, potentially protect perfused working hearts (Hattori et al, 2002), although RS failed to show such protective effect in nitric oxide synthase knockout mice (Imamura et al, 2002).…”
Section: Role Of Rs On Production Of Vasodilators and Vasoconstrictorsmentioning
confidence: 95%